Meta-Analysis the Effect of Cord Clamping Time on Hemoglobin Elevation in Newborn Infants - Dilafa, Rynda Arum; Rahardjo, Setyo Sri; Murti, Bhisma (Journal of Maternal and Child Health, 2023)
Background: Fulfillment of iron needs is very important in the first 1000 days of human life, with sufficient amounts of iron can determine the quality of life in the future, to produce a healthy and quality generation. Delaying clamping and cutting the umbilical cord for about 1-2 minutes can increase the amount of blood flowing to the newborn so as to prevent low hemoglobin in the neonatal period. This study aims to analyze the effect of delayed cord cutting on hemoglobin levels in newborns. Subjects and Method: This study was a systematic study and meta-analysis, with the following PICO Population= term newborn at 48 hours after birth. Intervention= Time delay of clamping the umbilical cord (≤60 seconds). Comparison= Immediate cord clamping time (≤15 seconds). Outcome= Hemoglobin Level. The articles used in this study were obtained from several databases including PubMed, Science Direct and Google Scholar. The keywords used were: “umbilical cord and infant”, “Delayed Cord Clamping”, “Delayed Cord Clamping and Immediate Cord Clamping” “DCC and Hemoglobin “DCC and Anaemia”. Inclusion criteria were full-text articles of randomized controlled experimental study design. trial (RCT) Articles were collected using PRISMA flow diagrams Articles were analyzed using the Review Manager 5.3 application. Results: Based on the results of a meta-analysis of 9 primary studies on the effect of cord clamping time on increasing newborn hemoglobin levels originating from Pakistan, China, Thailand, India, Bangladesh, the United States, and Nigeria, it can be concluded that delayed cord clamping in newborns birth increased the hemoglobin level by 0.81 units compared to clamping the cord immediately after birth, and this result was statistically significant (SMD= 0.81; 95% CI= 0.30 to 1.32; p=0.002). Conclusion: Delay in cutting the umbilical cord can increase hemoglobin in full-term newborns without indications. Keywords: delayed cord clamping, hemoglobin. Correspondence: Rynda Arum Dilafa. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: ryndaarumd@gmail.com. Mobile: +6285852358033